Formuły i algorytmy metody IRR - próba systematyzacji - Rogowski, Waldemar (Various IRR Algorithms - Attempt of Systematization, 2006)
Various IRR algorithms applied in evaluation of effectiveness of investment project are characterized in this paper. Mathematical form, economic interpretation and methods of building in criteria are also presented in this work. The author describes the origin of conflict between Hand NPV methods and he proves the argument that IRR method has many faces.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 516-527